2016
DOI: 10.1371/journal.pone.0160104
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Lodging-Related Traits along with Rice Genetic Improvement in China

Abstract: Rice yield potential was greatly improved since the green revolution, but the occurrence of lodging often restricts the achievement of potential yield. Currently, it is still obscure about how the lodging-related traits change along with the genetic improvement in yield potential of rice, although much efforts have been devoted to study the trend of and physiological mechanisms underlying changes in grain yield. Therefore, fourteen rice mega-varieties that were released and disseminated from 1930s to 2005 in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
1
22
1
1
Order By: Relevance
“…Subsequently, these genotypes showed higher grain yield at normal terminal drought situation than the grain yield at corresponding irrigated and KI sprayed environments. This is inconsistent with the findings of Zhu et al [17] that increased grain yield in rice varieties tolerant towards lodging.…”
Section: Comparison Of Grain Yield and Lodgingcontrasting
confidence: 99%
See 1 more Smart Citation
“…Subsequently, these genotypes showed higher grain yield at normal terminal drought situation than the grain yield at corresponding irrigated and KI sprayed environments. This is inconsistent with the findings of Zhu et al [17] that increased grain yield in rice varieties tolerant towards lodging.…”
Section: Comparison Of Grain Yield and Lodgingcontrasting
confidence: 99%
“…Lodging severity at maturity was scored visually on a scale of 0-9 [16,17], where 0 was totally upright and 9 was totally lodged, and given in the …”
Section: Data Recordingmentioning
confidence: 99%
“…Structural crop parameters, such as crop height, can also affect the lodging resistance of a variety and have been a central focus of seasonal crop lodging risk management (Pinthus, 1974). In the event of lodging, the plant structure is destroyed such that the stem is inclined at a certain angle, and plant height is reduced (Setter et al, 1997;Murakami et al, 2012;Zhu et al, 2016). Setter et al (1997) reported a reduction of 75% in rice canopy height under lodged conditions, which consequently lowered the photosynthesis rate by 60-80% relative to nonlodged rice.…”
Section: Factors Affecting Crop Lodgingmentioning
confidence: 99%
“…The brown color of rice seed pericarps is known to be related to the Rc gene, which encodes a trans-acting regulatory factor with a basic helix-loop-helix motif (Furukawa et al 2006). Unlike shattering habit and seed color, lodging habit is affected by quantitative traits such as culm length, culm thickness, culm stiffness, culm fresh weight, and internode diameter (Ookawa et al 2010;Zhu et al 2016). In rice, the semi-dwarf gene, sd1, increases yield by enhancing lodging resistance (Ashikari et al 2002).…”
Section: Introductionmentioning
confidence: 99%